Tracked Changes. Fibre optic interconnecting devices and passive components. Basic test and measurement procedures. Examinations and measurements. Withdrawal force from a resilient alignment sleeve using pin gauges Part 3-33, (23rd May 2022) - British Standards Institution,
No abstract available